Herzbergâ€™s Theory In Libyan Environment - Efhialelbum, Abderahman (Mediterranean Journal of Social Sciences, 2012)
Herzbergâ€™s motivation-hygiene theory is a popular but controversial theory of employee satisfaction. This theory has classifiedfactors that influence employeesâ€™ satisfaction into two categories â€œMotivators and Hygiene factorsâ€. The theory was at the centre of along debate that focused on conceptual and methodological problems. The objective of this comparative study is to understand both thehygiene factors and the motivators in the Libyan environment. The study aims to give a clear picture about the impact of implementingAmerican theories of motivation in different environments. A ratio analysis method has been used in this study; where ratio > 50 percentillustrates positive relation with a theoryâ€™s factor, ration < 50 percent indicates inverse relation. The findings support Herzberg Two-Factortheory of work motivation, where all motivators defined by Herzberg were found to be significant satisfiers (motivators) in the Libyanworkplace environments. On the other hand, some differences were found in the hygiene factors; thus these factors have been changedinto motivators due to the differences between the two environments. Furthermore, the study recommends that, to avoid the dominanceof the American theories it is important to develop culturally appropriate theories.